2020
DOI: 10.1016/j.bioorg.2019.103496
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of novel Imidazo[2,1-b]thiazole derivatives as potent antiviral and antimycobacterial agents

Abstract: A B S T R A C TA series of novel acyl-hydrazone (4a-d) and spirothiazolidinone (5a-d, 6a-d) derivatives of imidazo[2,1-b] thiazole were synthesized and evaluated for their antiviral and antimycobacterial activity. The antituberculosis activity was evaluated by using the Microplate Alamar Blue Assay and the antiviral activity was evaluated against diverse viruses in mammalian cell cultures. According to the biological activity studies of the compounds, 5a-c displayed hope promising antitubercular activity, 6d w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Gürsoy et al [149] synthesized a series of novel acyl-hydrazone and spirothiazolidinone ( 97a-d, 98a-d) derivatives of imidazo[2,1-b] thiazole and evaluated their antiviral activity (Figure 38). The study revealed that among all compounds tested, only compound 98d exhibited very good activity against Feline corona virus in CRFK cells, with an EC 50 value of 4.8 µM and SI more than 20, being much more potent than ganciclovir, used as reference drug (EC 50 value of >100 µM).…”
Section: Thiazole Derivatives As Antiviral Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gürsoy et al [149] synthesized a series of novel acyl-hydrazone and spirothiazolidinone ( 97a-d, 98a-d) derivatives of imidazo[2,1-b] thiazole and evaluated their antiviral activity (Figure 38). The study revealed that among all compounds tested, only compound 98d exhibited very good activity against Feline corona virus in CRFK cells, with an EC 50 value of 4.8 µM and SI more than 20, being much more potent than ganciclovir, used as reference drug (EC 50 value of >100 µM).…”
Section: Thiazole Derivatives As Antiviral Agentsmentioning
confidence: 99%
“…The best activity among all mentioned compounds was achieved for compound 150 with 96% inhibition followed by 153 and 154b with 94% and 92% of edema inhibition, respectively. For 4,7dihydrothiazolo [4,5-b]pyridine derivatives as well as pyridazine derivatives, the beneficial for activity was the presence of 4-chlorophenyl moiety (148), while for the thieno [3,2d]thiazole derivatives, the presence of the 3-cyano group (149) was more favorable than the presence of the COOEt moiety (149). For the thiazolo [4 ,5 :4,5]thieno [2,3-d]pyrimidine derivatives, a positive effect was observed with the presence of the hydroxyl group (150), while for arylhydrazone derivatives, the unsubstituted derivatives showed the best activity.…”
Section: Thiazoles As Antiflammatory Agentsmentioning
confidence: 99%
“…Hydrazide-hydrazone 39 was found to be most active against M. tuberculosis H37Rv (MIC = 16.252 µg/mL) and had no cytotoxicity towards CRFK (Crandell Rees feline kidney) cells (CC 50 > 100 µg/mL). However, its activity was lower than for rifampicin, which was used as a reference substance (MIC = 0.125 µg/mL) (Figure 31) [41]. New 1,3-oxazole-isoniazid hybrids synthesized by Shah et al were evaluated for their antitubercular activity against M. tuberculosis H37Rv strain.…”
Section: Antimycobacterial Activitymentioning
confidence: 99%
“…The authors discovered that compounds bearing methoxy groups in the phenyl ring attached to the 1,3-oxazole scaffold displayed better activity compared to the other compounds (Figure 32). Synthesized substances (40,41) were tested in vitro for cytotoxicity in human embryonic kidney (HEK-293T) cells and did not display changes in cytotoxicity as compared with vehicle (DMSO) [42].…”
Section: Antimycobacterial Activitymentioning
confidence: 99%
“…5 It is known that thiazole derivatives many compounds have exhibited remarkable antimycobacterial activity. [19][20][21][22][23][24][25][26] Moreover, thiazole derivatives have also exhibited a wide range of other pharmacological activity such as antimicrobial, 27,28 anti-inflammatory, 29 CNS active agents, 30 antimalarial 31 and anticancer 32 activities. Additionally, compounds bearing the pyrazole skeleton have been exhibited to exhibit significant antimycobacterial activity, [33][34][35] as well as antimicrobial, 36 anti-inflammatory 37 anticancer 38 and antimalarial 39 activities.…”
Section: Introductionmentioning
confidence: 99%